2020
DOI: 10.1111/luts.12336
|View full text |Cite
|
Sign up to set email alerts
|

TANGO” nocturia scanning tool: Turkish validity and reliability study

Abstract: Background: The aim of this study is to evaluate the validity and reliability of the Targeting the Individual's Aetiology of Nocturia to Guide Outcomes (TANGO) screening tool, which is used to determine nocturia etiology. Methods: Patients hospitalized in urology, orthopedics, and general surgery clinics between September 2019 and January 2020 were included in the study. Demographic characteristics of the participants such as age, gender, drug use, and nocturia severity were assessed by the researchers. The Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…4 In the paper of Culha et al there was a single group of 124 patients presenting a total Kappa value of 0.715 (individual item score weighted kappa coefficients, 0.696-0.731). 6 There is a strong correlation between nocturia and the nocturia index in men seeking LUTS treatment or in community-dwellers with or without LUTS. It has been supposed that the severity of nocturia correlates poorly with maximum bladder storage during the night but moderately corresponds with nocturnal polyuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In the paper of Culha et al there was a single group of 124 patients presenting a total Kappa value of 0.715 (individual item score weighted kappa coefficients, 0.696-0.731). 6 There is a strong correlation between nocturia and the nocturia index in men seeking LUTS treatment or in community-dwellers with or without LUTS. It has been supposed that the severity of nocturia correlates poorly with maximum bladder storage during the night but moderately corresponds with nocturnal polyuria.…”
Section: Discussionmentioning
confidence: 99%
“…However, Culha et al described the same methodology in validating TANGO questionnaire in the Turkish language. 6 Finally, a possible limitation is that patients and community-dwellers were not evaluated with the translated questionnaire after the prescribed nocturia management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturia is one of the lower urinary tract symptoms, which negatively affects patients' quality of life by causing frequent awakening at night but can be controlled when its cause is identified and treated (Culha et When the nocturia effects of long-term COVID-19 were examined according to the TANGO tool in this study, urinary tract was found as the 'priority' aetiological condition, which was followed by sleep, well-being, and cardio-metabolic factors. Items under the 'Urinary tract' factor on the TANGO nocturia screening tool express the presence of voiding dysfunction due to OAB and enlargement of the prostate and the frequency of nocturia (Bower et al, 2017;Culha et al, 2021). Some studies have shown that symptoms of OAB increase in patients who have experienced COVID-19, and that these symptoms include LUTS, such as urgency, increased frequency and nocturia (Can, Erkoc, et al, 2021;Dhar et al, 2020;Lamb et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although nocturia is defined as waking up at night and having to urinate at least once, it is among the most common lower urinary system symptoms (LUTS) that mostly affect the quality of life (Pesonen et al., 2020). Nocturia may be the first symptom of various hypervolemic states, age‐related changes in medications, changes in lifestyle and sleep quality, as well as serious systemic cardiovascular, respiratory, endocrine and metabolic diseases (Culha et al., 2021; Dutoglu et al., 2019). There is a lack of standardisation in defining the causes of nocturia (Graham Jr. et al., 2014).…”
Section: Introductionmentioning
confidence: 99%